Glomeruloid Microvascular Proliferation, Desmoplasia, and High Proliferative Index as Potential Indicators of High Grade Canine Choroid Plexus Tumors. Issue 3 (May 2018) - Muscatello, Luisa Vera; Avallone, Giancarlo; Serra, Fabienne; Seuberlich, Torsten; Mandara, Maria Teresa; Sisó, Silvia; Brunetti, Barbara; Oevermann, Anna
Choroid plexus tumors (CPT) are intraventricular neoplasms accounting for 10% of all primary central nervous system tumors in dogs. They are frequently classified according to the human WHO classification into choroid plexus papilloma (CPP, grade I), atypical CPP (aCPP, grade II), and choroid plexus carcinoma (CPC, grade III). Histological features observed in canine CPT such as increased vascular density (IVD) and glomeruloid microvascular proliferation (GMVP) are not part of the WHO classification. This multi-centric study aimed to investigate tumor-associated vascular hyperplasia in dogs by determining the prevalence of GMVP and IVD in 52 canine CPT and their association with tumor grade. In addition, the expression of angiogenic factors was assessed by immunohistochemistry in 25 tumors to investigate the pathogenesis of tumor-associated vascular hyperplasia. Based on the classical histological hallmarks, this study of 52 CPT identified 22 (42%) CPP (grade I) and 30 of (58%) CPC (grade III). GMVP was more prevalent in CPC (13/30; 43%) than CPP (1/22; 4%), whereas IVD occurred to a similar extent in CPP and CPC. Desmoplasia was more common in CPC (19/30; 63%) than CPP (2/22; 9%), and similarly, the proliferative index (PI) of neoplastic epithelium was significantly higher in CPC (5.14%) than CPP (0.94%). The majority of CPT expressed platelet-derived growth factor (PDGF), PDGFRα, PDGFRβ, and vascular endothelial growth factor (VEGF) irrespective of tumor grade or tumor-associated vascular hyperplasia. These results suggest that tumor-associated GMVP, desmoplasia, and PI may serve as histological indicators of malignancy in CPT.